Metal levels in street sediment from an industrial city: Spatial trends, chemical fractionation, and management implications - Kim N. Irvine (2018)
Background, aim and scope Street sediment samples were collected at 50 locations in a mixed land use area of Hamilton, Ontario, Canada, and metal levels were analyzed using a sequential extraction procedure for different particle size classes to provide an estimate of potential toxicity as well as the potential for treatment through best management practices (BMPs). Methodology The street sediment samples were dry sieved into four different particle size categories and a sequential extraction procedure was done on each size category following the methodology proposed by Tessier et al. 1979 using a Hitachi 180-80 Polarized Zeeman Atomic Absorption Spectrophotometer. Results and discussion Analysis of variance, post hoc least-significant difference tests, and kriging analysis showed that spatially Mn and Fe levels were associated with a well-defined heavy industrial area that includes large iron-and steel-making operations; Cu and Pb were associated with both the industrial and high-volume traffic areas, while Zn tended to be more associated with high-volume traffic areas. The potential bioavailability of the metals, based on the sum of chemical fractions 1 (exchangeable) and 2 (carbonate-bound), decreased in order: Zn > Cd > Mn > Pb > Cu > Fe. Based on aquatic sediment quality guidelines, there is some concern regarding the potential impact of the street sediment when runoff reaches receiving waters. Conclusions It is possible that a combination of BMPs, including street sweeping and constructed wetlands, could help to reduce street sediment impact on environmental quality in the Hamilton region. The data presented here would be important in developing and optimizing the design of these BMPs. © Springer-Verlag 2009.